PENGARUH EDUKASI KESEHATAN DENGAN MEDIA LEAFLET TERHADAP TINGKAT PENGETAHUAN REMAJA TENTANG PENYAKIT MENULAR SEKSUAL DI SMP MUTIARA INSAN NUSANTARA - velia agustin velia (Jurnal Riset Media Keperawatan, 2026)
Sexually Transmitted Diseases are a growing public health problem, including in Indonesia. This increase is driven by lifestyle, risky sexual behavior, and, particularly among adolescents, low knowledge about Sexually Transmitted Diseases. To analyze the influence of health education with leaflet media on the level of adolescent knowledge about sexually transmitted diseases at SMP Mutiara Insan Nusantara. quantitative with Pre-Experimental design approach. Using one group pretest-posttest design. With a population of 64 respondents and using non-probability sampling samples with a purposive sampling approach of 61 samples. in this study using the Wilcoxon Signed Ranks Test because the data is not normally distributed with a significant value of 000<0,05, and then using the Wilcoxon Signed Ranks Test the result is an Asymp value. Sig (2-tailed) 0.000 is smaller than the probability (0.000 < 0.05) so it can be concluded that the result of Ho is rejected and Ha is accepted (Meaning that there is the influence of health education with leaflet media on the level of knowledge of teenagers about sexually transmitted diseases at Mutiara Insan Nusantara Junior High School). Keywords : Health education, Leaflet, Knowledge level, Teenagers, Sexually transmitted diseases